Inactivation of antibiotic resistant bacteria by nitrogen-doped carbon quantum dots through spontaneous generation of intracellular and extracellular reactive oxygen species - Weibo Xia; Zixia Wu; Bingying Hou; Zhang Cheng; Dechuang Bi; Luya Chen; Wei Chen; Heyang Yuan; Leo H. Koole; Lei Qi (Materials Today Bio)
The widespread antibiotic resistance has called for alternative antimicrobial agents. Carbon nanomaterials, especially carbon quantum dots (CQDs), may be promising alternatives due to their desirable physicochemical properties and potential antimicrobial activity, but their antimicrobial mechanism remains to be investigated. In this study, nitrogen-doped carbon quantum dots (N-CQDs) were synthesized to inactivate antibiotic-resistant bacteria and treat bacterial keratitis. N-CQDs synthesized via a facile hydrothermal approach displayed a uniform particle size of less than 10 nm, featuring a graphitic carbon structure and functional groups including -OH and -NH2. The N-CQDs demonstrated antimicrobial activity against Staphylococcus aureus (S. aureus) and methicillin-resistant S. aureus, which was both dose- and time-dependent, reducing the survival rate to below 1 %. The antimicrobial activity was confirmed by live/dead staining. In in vivo studies, the N-CQDs were more efficient in treating drug-resistant bacterial keratitis and reducing corneal damage compared to the common antibiotic levofloxacin. The N-CQDs were shown to generate intracellular and extracellular ROS, which potentially caused oxidative stress, membrane disruption, and cell death. This antimicrobial mechanism was supported by scanning and transmission electron microscopy, significant regulation of genes related to oxidative stress, and increased protein and lactate dehydrogenase leakage. This study has provided insight into the development, application, and mechanism of N-CQDs in antimicrobial applications.